1983
DOI: 10.1159/000176721
|View full text |Cite
|
Sign up to set email alerts
|

Digestion of Maltitol in Man, Rat, and Rabbit

Abstract: Maltitol is found to be enzymatically hydrolyzed by the small intestinal mucosa of man, rat, and rabbit and metabolized by everted sacs of rabbit intestine at a moderate rate. On in vivo perfusion of maltitol (15.3 µmol/min) through the small intestine, 19% of the sugar alcohol is digested by gnotobiotic rats. 120 min after stomach intubation of gnotobiotic rats, only 31% of the ingested maltitol is found in the ileum. A daily application of 35 g maltitol to 4 human beings does not influence the parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The liberated glucose molecules are absorbed virtually completely, whereas the liberated d -glucitol is incompletely absorbed, contributes to osmotic diarrhea, and is eventually subject to microbial fermentation in the gut. Zunft et al [44] showed already in 1983 that maltitol will be digested and utilized by man, rat, and rabbit. A daily application of 35 g maltitol to humans “did not influence the parameters of well-being, compatibility, and fecal state.”…”
Section: Also Disaccharide Sugar Alcohols May Cause Osmotic Diarrheamentioning
confidence: 99%
“…The liberated glucose molecules are absorbed virtually completely, whereas the liberated d -glucitol is incompletely absorbed, contributes to osmotic diarrhea, and is eventually subject to microbial fermentation in the gut. Zunft et al [44] showed already in 1983 that maltitol will be digested and utilized by man, rat, and rabbit. A daily application of 35 g maltitol to humans “did not influence the parameters of well-being, compatibility, and fecal state.”…”
Section: Also Disaccharide Sugar Alcohols May Cause Osmotic Diarrheamentioning
confidence: 99%
“…The ma jority of these materials are polyols, or else contain polyols, and their gastro-intestinal effects at high lev els of intake, resulting from the lack of active ab sorptive mechanisms in mammals, are well known, leading to osmotic disturbance of water balance and increased water intake. Signs of this were more prom inent on a sorbitol regimen than with the same pro portion of Lycasin 80/55 in the diet, but it is still a factor to be taken into account in the formulation of foodstuffs containing Lycasin 80/55, which contains 8% of sorbitol and 53% of maltitol (table IV), even though the maltitol may be hydrolyzed enzymically and then digested [Zunft et al, 1983;Rosiers et al, 1985].…”
Section: Discussionmentioning
confidence: 99%
“…The published values for the Michaelis constant (K m ) and the maximum reaction rate (V max ) differ tremendously, probably because individual researchers have worked with substrates of varying purity [273].…”
Section: Maltitolmentioning
confidence: 99%